The Effectiveness of Using Edlink in Increasing Student Motivation to Learn at Nusa Putra University - Mintawati, Hesri; Supriadi, Saffana Azka; Nazareina, Leisya Putri; Aulia, Restu Nur; Nurohmah, Vinda Amelia (Neolectura, 2024)
This study aims to determine the effectiveness of using Edlink on learning motivation of Nusa Putra University students. The research method used is qualitative interview with respondents as many as 20 students of Nusa Putra University who use Edlink as a learning media. The results showed that the students felt that Edlink helped them to be more active and organized in learning. The use of Edlink at Nusa Putra University has had a significant impact on students' learning process. Based on the interviews conducted, students generally see Edlink as a practical and efficient platform, capable of supporting their lecture needs. The main advantages perceived by students are the ease of access, flexibility, and integration of features that help organize assignments and lecture materials well.